2021
DOI: 10.1111/1742-6723.13905
|View full text |Cite
|
Sign up to set email alerts
|

‘You can make change happen’: Experiences of emergency medicine leadership in the Pacific

Abstract: Objective: We sought to explore the activities, responsibilities and experience of leadership from Pacific emergency medicine (EM) doctors. Additionally, we explored knowledge, attitudes, leadership gaps and training insights for individual clinicians, and from a Pacific regional perspective. Methods: This was a qualitative study using in-depth, semi-structured interviews of invited Pacific EM doctargeted leadership training and contribute to building Pacific regional networks for career sustainability and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“… 36 , 37 Recent research has demonstrated the importance of regional collaboration in effective emergency care development, and the value of enduring mentoring relationships between Pacific and global colleagues. 16 , 38 , 39 , 40 Long-term partnerships are essential to building trust and cross-cultural understanding, and can provide a foundation for the type of training program described here.…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 Recent research has demonstrated the importance of regional collaboration in effective emergency care development, and the value of enduring mentoring relationships between Pacific and global colleagues. 16 , 38 , 39 , 40 Long-term partnerships are essential to building trust and cross-cultural understanding, and can provide a foundation for the type of training program described here.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with what we know of Pacific EC leaders prior to the pandemic who demonstrated maturity and vision despite relative youth and inexperience, and their pre-pandemic ability to mobilise teams through leveraging goodwill, solidarity and regional support. 12 Before and during the COVID-19 outbreak, EC clinician leadership is sustained and enhanced through regional networks of professional and personal support, such as the Pacific online EC support network which underpinned stage one of this research. 22…”
Section: Discussionmentioning
confidence: 99%
“…Health leadership is also essential to creating cultures of safety to improve quality patient and community outcomes, in EC specifically 12 , 23 and in emergency and disaster contexts generally. 24 This is important to note given the disproportionate number of natural emergencies and disasters that the Pacific Island region annually experiences compared to other global regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic has turned spotlights on both the strengths and weaknesses of EC systems in the Pacific region: the lack of coordination and capacity in many countries, the need for well organised and adequately-resourced facility-based EC, and the dedication, skills and leadership of EC clinicians. 23 This study's findings further demonstrate that EC clinicians are assets to health systems and leaders in emergency preparedness and surge responses. 24,25 As one explained, EC clinicians are "the frontliners of the frontliners in the hospital"; the emergence of COVID-19 meant their roles were more valued because "it made a difference to the rest of the hospital who we allowed in and who we didn't".…”
Section: Lesson 3 Ec Systems Were Central and Strong Ec Clinicians Le...mentioning
confidence: 53%